Exploring how infectious diseases control interventions are delivered in low-income urban communities in low- and middle-income countries: A scoping review protocol - Hammed O. Mogaji; Ifrah A. Fatah; Scott C. Dorris; Margaret C. Baker (PLoS ONE, 2025)
Infectious diseases thrive in densely populated low-income urban communities where living conditions, hygiene, and access to health services are sub-optimal. Information on how to adapt infectious diseases control interventions to be effective in these settings is limited. The proposed scoping review will follow Joanna Briggs Institute (JBI) guidelines and the PRISMA methodology adapted for scoping reviews (PRISMA-ScR). Research questions were created using the Person, Concept, Context (PCC) framework. In this study, person refers to low-income urban communities, concept refers to community-based infectious disease interventions adapted to their setting, and the context is low- and middle-income countries. Relevant papers published after 2000 will be retrieved using a search strategy that incorporates all the PCC topics. Searches will be made in four databases: MEDLINE, Embase, Global Health (all via Ovid), and Web of Science. Duplicates will be identified and removed with EndNote 20, and all articles will be uploaded into Covidence for screening in two stages using pre-defined inclusion and exclusion criteria. Quantitative and qualitative data will be extracted into Excel spreadsheets and analyzed. Our review will identify different approaches that have been taken to adapt infectious disease interventions in low-income urban communities of LMICs that can be further tested in future programs and studies. We will also highlight methods that have been used to study such interventions in their context.